2010
DOI: 10.3109/10520290903162730
|View full text |Cite|
|
Sign up to set email alerts
|

Exfoliative cytology for diagnosing oral cancer

Abstract: Exfoliative cytology is a minimally invasive technique for obtaining oral cell specimens from patients for diagnostic purposes. Classical applications of oral cytology studies, such as oral candidiasis, have been extended to include oral precancerous and cancerous lesions. A number of analytical methods are available for studying cytology specimens. The development of molecular analysis techniques, the oral cancer etiopathogenic process, and improvements in liquid-based exfoliative cytology are leading to rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Oral cytology is useful for monitoring patients undergoing treatment in order to guide the selection of sites for incisional biopsies (26,27) and to analyze lesions with malignant potential with high sensitivity and specificity, leading to an early diagnosis (28). In addition, oral cytology has been used to identify changes prior to their clinical visibility (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cytology is useful for monitoring patients undergoing treatment in order to guide the selection of sites for incisional biopsies (26,27) and to analyze lesions with malignant potential with high sensitivity and specificity, leading to an early diagnosis (28). In addition, oral cytology has been used to identify changes prior to their clinical visibility (27).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, oral cytology has been used to identify changes prior to their clinical visibility (27). The advantages of exfoliative cytology make it a particularly useful diagnostic method for obtaining early test results.…”
Section: Resultsmentioning
confidence: 99%
“…[1920] Other researchers have found cytomorphometric changes in the cells of the oral mucosa of smokers, similar to those found in diabetics, caused by the chronic inflammation of the oral mucosa. Changes in the oral mucosa similar to those appearing in individuals with type 2 diabetes have also been found in patients with Vitamin B12 and folic acid nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 64%
“…[181920] There is currently no cytological study on chronic and aggressive periodontal disease; nevertheless, our research has shown that the cytological study of the soft wall of the pocket shows tissue damage as an increase in inflammatory cells, cells from deep layers of the epithelium, and disease-related microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant changes take place at a molecular level before they are visible under the microscope or before any clinical changes occur. Therefore, exfoliative cytology has lately gained great importance as a rapid, painless and simple method for obtaining RNA samples from such suspicious mucosal lesions in order to carry out highly sensitive molecular diagnostic methods 2,3 . Early diagnosis of high‐risk oral premalignant lesions can reduce the mortality, morbidity and also the cost of treatment.…”
Section: Introductionmentioning
confidence: 99%